Autocenral series and n-autoisoclinism of groups - Sepehrizadeh, Zohreh; Rismanchian, Mohammad Reza (Indian journal of pure and applied mathematics, 2025)
In 1976 Bioch introduced the concept of n-isoclinism of groups. Using the definition of absolute centre and autocommutator subgroup of a group introduced by Hegarty, the notion of autoisoclinism has been studied in the recent years. In this article we first derive some results from definition of Hegarty. Then we introduce the concept of n-autoisoclinism, and obtain some basic results similar to n-isoclinism.